Differences in physical performance between Olympic and non-Olympic female rugby sevens players - Loturco, I.; Pereira, L. A.; Arruda, A. F.; Reis, V. P.; Robineau, J.; Couderc, A.; Guerriero, A.; Freitas, T. T. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study compared the physical performance of National female rugby sevens players selected or not selected to form the Brazilian National Olympic team. METHODS: Thirty women rugby sevens players from the Brazilian National team (15 Olympic and 15 non-Olympic athletes) participated in this study. Tests were performed on consecutive days, in the following order: day 1) standing long jump (SLJ); squat and countermovement jumps (SJ and CMJ); and one-repetition maximum test in the bench-press, prone-row, and parallel squat exercises; day 2) 40-m linear sprint; Pro-agility and L-drill change of direction tests; and Yo-Yo intermittent recovery test level 1 (IR1). The differences between groups in all variables examined were analyzed using the independent t test and effect sizes (ES). RESULTS: Greater jump performances were noticed for the Olympic players in all jump tests compared to the non-Olympics (ES=0.95, ES=1.05, and ES=0.93, for SLJ, SJ, and CMJ, respectively; P<0.05). Olympics revealed shorter sprint times than non-Olympics in 40-m distance (ES=0.88; P<0.05). Higher one-repetition maximum in the bench-press and Yo-Yo IR1 distance were also observed for the Olympics in comparison to non-Olympic players (ES=0.65 and 0.93, respectively; P<0.05). CONCLUSIONS: Lower-body power, upper-body strength, maximal sprint velocity and aerobic fitness were found to be important for distinguishing between Olympic and non-Olympic female rugby sevens players. Coaches and practitioners should prioritize the development of these physical qualities in these team-sport athletes.